Allan Ramsay and the Search for Horace's Villa - Gordon Brown, Ian (Routledge Revivals, 2017)
"Cover" -- "Half Title" -- "Title Page" -- "Copyright Page" -- "Table of Contents" -- "List of Text Illustrations" -- "List of Colour Plates" -- "List of Abbreviations" -- "Notes on Contributors" -- "Preface by the Series Editor" -- "Preface and Acknowledgements" -- "Introduction" -- "1 Allan Ramsay: Artist, Author, Antiquary" -- "2 Some Reflections on the Idea of Horace's Farm" -- "3 Describing the Villa: un rêve virgilien" -- "4 Illustrating Horace's Villa: Allan Ramsay, Jacob More and Jakob Philipp Hackert" -- "5 Ramsay's 'Enquiry': Text and Context" -- "6 A Note on the Text of Ramsay's 'Enquiry'" -- "7 An Enquiry into the Situation and Circumstances of Horace's Sabine Villa Written during travels through Italy in the years 1775, 76, and 77" -- "8 Catalogue: Illustrative WorksRelating to Allan Ramsay's Search for Horace's Villa" -- "Bibliography".